Rapid peat development beneath created, maturing mangrove forests: ecosystem changes across a 25‐yr chronosequence. Issue 4 (2nd March 2020) - Osland, Michael J.; Feher, Laura C.; Spivak, Amanda C.; Nestlerode, Janet A.; Almario, Alejandro E.; Cormier, Nicole; From, Andrew S.; Krauss, Ken W.; Russell, Marc J.; Alvarez, Federico; Dantin, Darrin D.; Harvey, James E.; et al.
Abstract: Mangrove forests are among the world's most productive and carbon‐rich ecosystems. Despite growing understanding of factors controlling mangrove forest soil carbon stocks, there is a need to advance understanding of the speed of peat development beneath maturing mangrove forests, especially in created and restored mangrove forests that are intended to compensate for ecosystem functions lost during mangrove forest conversion to other land uses. To better quantify the rate of soil organic matter development beneath created, maturing mangrove forests, we measured ecosystem changes across a 25‐yr chronosequence. We compared ecosystem properties in created, maturing mangrove forests to adjacent natural mangrove forests. We also quantified site‐specific changes that occurred between 2010 and 2016. Soil organic matter accumulated rapidly beneath maturing mangrove forests as sandy soils transitioned to organic‐rich soils (peat). Within 25 yr, a 20‐cm deep peat layer developed. The time required for created mangrove forests to reach equivalency with natural mangrove forests was estimated as (1) <15 yr for herbaceous and juvenile vegetation, (2) 55 yr for adult trees, (3) 25 yr for the upper soil layer (0–10 cm), and (4) 45–80 yr for the lower soil layer (10–30 cm). For soil elevation change, the created mangrove forests were equivalent to or surpassed natural mangrove forests within the first 5 yr. A comparison to chronosequence studies from other ecosystems indicates that the rate of soil organic matter accumulation beneath maturing mangrove forests may be among the fastest globally. In most peatland ecosystems, soil organic matter formation occurs slowly (over centuries, millennia); however, these results show that mangrove peat formation can occur within decades. Peat development, primarily due to subsurface root accumulation, enables mangrove forests to sequester carbon, adjust their elevation relative to sea level, and adapt to changing conditions at the dynamic land–ocean interface. In the face of climate change and rising sea levels, coastal managers are increasingly concerned with the longevity and functionality of coastal restoration efforts. Our results advance understanding of the pace of ecosystem development in created, maturing mangrove forests, which can improve predictions of mangrove forest responses to global change and ecosystem restoration.